The Effect of Brand Awareness and Promotion Strategy on Purchasing Decisions at ITB Press - Fikky Sherlinadya; Novi Rukhviyanti (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of brand awareness and promotional strategies on purchasing decisions for ITB Press products. The research method uses a quantitative approach with data collection techniques through a questionnaire using a 5-point Likert scale. Data were analyzed using SPSS version 29 with validity, reliability, normality, and multiple linear regression tests. Simultaneously, the results of the study prove that brand awareness and promotional strategies together have a significant effect on purchasing decisions. Partially, both variables also showed a positive and significant influence on purchasing decisions at ITB Press, with promotional strategies making a more dominant contribution than brand awareness. The findings provide practical implications for ITB Press to optimize integrated marketing strategies with a focus on strengthening digital promotions and increasing brand awareness.